A Challenges in Measuring the Effectiveness of Public Organizations: A Review of Selected Models - Zofia Gródek-Szostak; Henryk Gurgul; Nina Dubiel (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
Against the backdrop of a turbulent environment and changing economic, social, and technological realities, public sector organizations are facing the challenge of improving the effectiveness of their operations. The concept of New Public Management (NPM), drawing from private sector solutions, has significantly contributed to the reorganization of public administration through workforce reduction, decentralization, and privatization, with a focus on performance management. Academic literature continues to seek answers regarding the internal and external conditions for measuring effectiveness in public institutions, including higher education institutions.